Production systems of swine in the rural areas of Rangamati and Khagrachari districts of Bangladesh - Hossain, ME; Chakma, S; Khatun, MM; Hasanuzzaman, M; Miah, MY; Biswas, MAA (Bangladesh Journal of Animal Science, 2012)
The study was undertaken for a period of 60 days to investigate the production systems of swine in Rangamati and Khagrachari districts, Bangladesh. Production systems, particularly housing, feeding, breeding, disease prevalence, vaccination, bio-security, marketing, socio-economic condition and constraints of pig production were investigated during the study period. It was found that the propensity of rearing pig differed significantly (P<0.01) among the pig owners. Pigs were reared mostly by poor and landless peoples (54.7%) followed by marginal (32.1%), medium (9.4%) and large (3.8%). Rearing systems were also different (P<0.01) and the mean figures were 43.4% for free range, 24.5% for tin shed housing , 20.8% for fencing and 11.3% for girth tethering systems. The average litter size, birth weight, post-weaning weight and weaning period were 9.3, 1.72 kg, 9.0 kg and 40.8 days respectively. Prevalence of diseases differed (P<0.01) and most prevalent diseases were diarrhea (35.8%), coccidiosis (20.8%), pneumonia (17.0%) and hemorrhagic septicemia (13.2%). The economic benefits generated from farming were selling of piglets. DOI: http://dx.doi.org/10.3329/bjas.v40i1-2.10787 Bang. J. Anim. Sci. 2011. 40 (1-2): 28-33